Metal complex acceptor material, exciplex thereof and application

By combining metal complexes with organic donor materials to construct the excitation composite, the problems of low efficiency and short life of organic light emitting diodes in the prior art are solved, and an efficient and long-life organic light emitting diode is realized, with commercial applications potential.

CN119219671AActive Publication Date: 2024-12-31ZHONGKAI UNIV OF AGRI & ENG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411343997.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing organic light emitting diodes have low efficiency and short service life. The pure organic exciton annihilation problem of luminescent excitons, and the metal complex TADF type excitation complex system has not received enough attention.

Method used

The metal complex acceptor material and organic donor material are used to construct the excitation composite luminescent material, which is used in organic light-emitting diodes to improve luminescence efficiency and reduce driving voltage and improve device life.

Benefits of technology

It realizes high luminous quantum yield and low starting voltage of organic light emitting diodes, significantly extending the service life of the device and has the potential for commercial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219671A_ABST
    Figure CN119219671A_ABST
Patent Text Reader

Abstract

The invention relates to a metal complex acceptor material, an exciplex thereof and application. The invention relates to a metal complex acceptor material, which is a compound with a structure as shown in a formula (I), the metal complex acceptor material is matched with an organic donor material to form an exciplex luminescent material, the exciplex luminescent material is applied to an organic light-emitting diode, the driving voltage is lower, the luminous efficiency is higher, and the service life of a device can be prolonged. The compound has potential to be applied to the field of organic electroluminescent devices. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of luminescent materials, and in particular to metal complex acceptor materials, exciplex luminescent materials containing metal complex acceptor materials, and applications thereof in organic light emitting diodes. Background Art

[0002] Organic optoelectronic devices include, but are not limited to, the following categories: organic light-emitting diodes (OLEDs), organic thin-film transistors (OTFTs), organic photovoltaics (OPVs), light-emitting electrochemical cells (LCEs), and chemical sensors.

[0003] In recent years, OLEDs, as a lighting and display technology with great application prospects, have received widespread attention from academia and industry. OLEDs devices have the characteristics of self-luminescence, wide viewing angle, short response time and the ability to prepare flexible devices, making them a strong competitor for the next generation of display and lighting technologies. However, OLEDs still have problems such as low efficiency and short life, which need further research. High-efficiency and long-life OLED devices usually require an optimized combination of device structure and functional layer materials. Common functional layer materials include: hole injection materials, hole transport materials, electron injection materials, electron transport materials, electron blocking materials, host materials and luminescent materials. In order to prepare OLEDs with better luminescence efficiency and longer device life, academia and industry have been committed to developing new luminescent materials.

[0004] The singlet-triplet energy gap (ΔE ST ) is small (<0.2eV), triplet excitons can be converted into singlet excitons through reverse intersystem crossing (RISC) to emit delayed fluorescence (TADF), and the internal quantum efficiency of the device can reach 100%. In addition, the exciplex can also reduce the driving voltage of the device, which has attracted widespread attention from the scientific research and industry circles. The exciplex systems currently reported in the literature are mainly based on pure organic electron donor and acceptor materials. The photophysical and electrochemical properties of common hole transport, electron transport and bipolar materials have been reported in detail. Combining these materials can realize the luminescence of the exciplex, and the external quantum efficiency (EQE) of the device is mostly between 5-20%. The delayed fluorescence lifetime (τ DF ) is generally long, which can easily lead to the annihilation of luminescent excitons, and at the same time have an adverse effect on the efficiency and stability of the device. In theory, using transition metal complexes (such as iridium, platinum, gold, palladium, copper, etc.) to construct an exciplex system can utilize the metal heavy atom effect and the interaction between the metal center and the ligand to obtain a high-efficiency luminescent material. However, compared with the above-mentioned pure organic donor-acceptor combination system, the current TADF-type exciplex system of metal complexes has not received enough attention from the academic community, and there are few related reports. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides a metal complex acceptor material, which can form an exciplex luminescent material with an organic donor material. The exciplex luminescent material is applied in an organic light-emitting diode, has a lower driving voltage and a higher luminous efficiency, and can improve the service life of the device.

[0006] The present invention also provides an organic light emitting diode based on the exciplex luminescent material.

[0007] Metal complex receptor material, a compound having the structure of formula (I):

[0008]

[0009] in:

[0010] R 1 To R 6 are substituents, each independently selected from the group consisting of deuterium, halogen, aldehyde, cyano, substituted or unsubstituted alkylsulfonyl having 1 to 6 carbon atoms, substituted or unsubstituted arylsulfonyl having 6 to 30 carbon atoms, substituted or unsubstituted alkyl having 1 to 6 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted alkoxy having 1 to 20 carbon atoms, substituted or unsubstituted aryl having 6 to 30 carbon atoms, substituted or unsubstituted heteroaryl having 3 to 30 carbon atoms, or any two adjacent substituents connected or fused to form a ring;

[0011] The heteroatom in the heteroaryl group is N, S or O, and the substitution is substitution by D, F, or C1-C4 alkyl;

[0012] M is selected from: gold, silver, palladium or copper; X1 and X2 are each independently C or N.

[0013] a1 to a4 are integers of 0-5, and when a1 is 2 or greater, two R 1 The groups are the same or different from each other. When a2 is 2 or greater, the two R 2 The groups are the same or different from each other. When a3 is 2 or greater, the two R 3 The groups are the same or different from each other. When a4 is 2 or greater, the two R 4 The groups are the same or different from each other;

[0014] a5 and a6 are integers of 0-4, and when a5 is 2 or greater, the two R 5 The groups are the same or different from each other. When a6 is 2 or greater, the two R 6 The groups are the same or different from each other;

[0015] When a1 to a6 are zero, R 1 To R 6 The substituent is absent, ie, there is no substituent on the corresponding aromatic ring or heteroaromatic ring.

[0016] Preferred: R 1 To R 6 Each is independently selected from the group consisting of deuterium, halogen, cyano, substituted or unsubstituted alkyl having 1 to 6 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted aryl having 6 to 30 carbon atoms, and substituted or unsubstituted heteroaryl having 3 to 30 carbon atoms.

[0017] Further preferred: R 1 To R 2 Each is independently selected from deuterium, halogen, substituted or unsubstituted alkyl having 1 to 6 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, and a3 to a6 are zero.

[0018] More preferably, both X1 and X2 are N.

[0019] More preferably, M is gold.

[0020] An exciplex luminescent material is composed of a metal complex acceptor material and an organic donor material in a mass ratio of 5% to 95%, wherein the organic donor material molecule has one of the following structures:

[0021]

[0022] Preferably, the composition is composed of 5%-20% of the gold complex acceptor material and 95%-80% of the organic donor material molecules in a mass ratio. More preferably, the composition is composed of 20% of the gold complex acceptor material and 80% of the organic donor material in a mass ratio.

[0023] The following are examples of metal complex receptor material molecules according to the present invention, but are not limited to the listed structures:

[0024]

[0025]

[0026]

[0027]

[0028]

[0029]

[0030]

[0031]

[0032]

[0033]

[0034]

[0035] The present invention also provides an application of an exciplex constructed based on the above-mentioned donor and acceptor combination in an organic optoelectronic device, wherein the optoelectronic device includes, but is not limited to, organic light emitting diodes (OLEDs), organic thin film transistors (OTFTs), organic photovoltaic devices (OPVs), light emitting electrochemical cells (LCEs) and chemical sensors, preferably OLEDs.

[0036] Organic light emitting diodes (OLEDs) include a cathode, an anode and an organic layer, wherein the organic layer is one or more of a hole injection layer, a hole transport layer, a light emitting layer, a hole blocking layer, an electron injection layer and an electron transport layer, and not all of these organic layers need to be present; at least one of the hole injection layer, the hole transport layer, the hole blocking layer, the electron injection layer, the light emitting layer and the electron transport layer contains the excimer complex.

[0037] The exciplex serves as a light-emitting material in the light-emitting layer.

[0038] The total thickness of the organic layer of the device of the present invention is 1-1000 nm, preferably 1-500 nm, more preferably 5-300 nm.

[0039] The organic layer may be formed into a thin film by evaporation or a solution method.

[0040] The present invention discloses a series of luminescent materials based on the exciplex of a metal complex acceptor and an organic donor, which show a relatively high luminescent quantum yield and have the potential to be applied to commercial organic light-emitting diode devices.

[0041] The use of the exciplex of the invention as the luminescent material of an organic electrophotoelectric device has the advantages of low device starting voltage and high luminescent efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 .Emission spectra of TAPC, complex 4 and 4:TAPC (20:80) thin films,

[0043] Figure 2 .Emission spectra of TAPC, complex 60 and 60:TAPC (20:80) films,

[0044] Figure 3.Emission spectra of TAPC, complex 116 and 116:TAPC (20:80) thin films

[0045] Figure 4 .The structure diagram of the organic light emitting diode device of the present invention, wherein 10 represents a glass substrate, 20 represents an anode, 30 represents a hole injection layer, 40 represents a light emitting layer, 50 represents an electron transport layer, 60 represents an electron injection layer, and 70 represents a cathode. DETAILED DESCRIPTION

[0046] The present invention does not require the synthesis method of the materials. In order to describe the present invention in more detail, the following examples are given, but are not limited thereto. The raw materials used in the following synthesis are all commercially available products unless otherwise specified.

[0047] Example 1: Synthesis of Complex 1

[0048] Synthesis of intermediate 1

[0049]

[0050] Dissolve chloroauric acid trihydrate (3.75 g, 9.52 mmol) in 6 mL of water and 30 mL of ethanol, and then add tetrahydrothiophene (2.10 mL, 23.81 mmol) dropwise. A thick yellow precipitate is immediately generated. Continue to add dropwise, and the solid turns white. Then add 24 mL of ethanol to make it easier to stir the reaction mixture. Stir at 40 ° C for 20 minutes, filter the white precipitate, wash with a large amount of ethanol, and remove the solvent in vacuo. Obtain 2.75 g of white solid. Yield 90%. MS (m / z): 321.58 (M+1)

[0051] Synthesis of compound 1a:

[0052]

[0053] Under nitrogen, palladium acetate (0.036 g, 0.339 mmol) and tri-tert-butylphosphine tetrafluoroborate (0.295 g, 1.017 mmol) were dissolved in 30 mL of toluene. Then 1,2-dibromobenzene (2.00 g, 8.48 mmol), aminobenzene (1.58 g, 16.96 mmol) and sodium tert-butoxide (3.26 g, 33.91 mmol) were added to the suspension and refluxed at 120 ° C for 12 h. After the reaction was completed, ammonium chloride solution was added, the liquid was extracted and separated, the organic phase was dried with anhydrous sodium sulfate, adsorbed on silica gel, and purified by column chromatography (dichloromethane: petroleum ether = 1:9). 1.503 g of solid was obtained. The yield was 68%. MS (m / z): 261.34 (M+1)

[0054] Synthesis of compound 1b:

[0055]

[0056] Compound 1a (2.00 g, 7.68 mmol) and NH4BF4 (0.926 g, 8.83 mmol) were added to 25 mL of triethyl orthoformate in a high pressure reactor, and then 2 mL of acetic acid was added. The resulting mixture was heated at 120 ° C for 12 h. After the reaction was completed, n-hexane was added, the solid was precipitated and filtered, and then ethyl acetate and methyl tert-butyl ether were used for pulping, and the solvent was removed in vacuo to obtain 2.063 g of solid. The yield was 75%. MS (m / z): 359.15 (M+1) Synthesis of compound 1c:

[0057]

[0058] Compound 1b (1.00 g, 2.79 mmol) was added to 17 mL THF under nitrogen, followed by 1.4 mL KHMDS (1 M in THF) at 0 °C. Stir for 20 min, return to room temperature, add intermediate 1 (0.895 g, 2.79 mmol), and react at 40 °C for 12 h. After the reaction, spin dry, dissolve in dichloromethane, filter on diatomaceous earth, slurry with dichloromethane: n-hexane (1:4), and remove the solvent in vacuo to obtain 0.525 g of solid. Yield 38%. MS (m / z): 503.76 (M+1)

[0059] Synthesis of complex 1:

[0060]

[0061] Compound 1c (0.450 g, 0.895 mmol), 2,4-diphenyl-6-[4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl]-1,3,5-triazine (0.354 g, 0.814 mmol) and potassium carbonate (0.562 g, 4.07 mmol) were added to 45 mL of ethanol under nitrogen atmosphere. The mixture was reacted at 40 °C for 12 h. After the reaction was completed, the solid was dissolved in dichloromethane and filtered through diatomaceous earth. The filtrate was rotary evaporated to solid and then slurried with dichloromethane: ethanol (1:4). The solvent was removed in vacuo to obtain 0.359 g of solid. The yield was 57%. MS (m / z): 776.67 (M+1)

[0062] Example 2: Synthesis of Complex 3

[0063] Synthesis of compound 3a:

[0064]

[0065] The synthesis of compound 3a is similar to compound 1a: 4-tert-butylaniline (2.53 g, 16.96 mmol) was used instead of aminobenzene. 2.560 g of solid was obtained with a yield of 81%. MS (m / z): 373.56 (M+1)

[0066] Synthesis of compound 3b:

[0067]

[0068] The synthesis of compound 3b was similar to compound 1b: compound 3a (2.00 g, 5.37 mmol) was used instead of compound 1a. 1.973 g of solid was obtained with a yield of 78%. MS (m / z): 471.36 (M+1)

[0069] Synthesis of compound 3c:

[0070]

[0071] The synthesis of compound 3c was similar to compound 1c: compound 3b (1.00 g, 2.13 mmol) was used instead of compound 1b. 0.406 g of solid was obtained with a yield of 31%. MS (m / z): 615.97 (M+1)

[0072] Synthesis of complex 3:

[0073]

[0074] The synthesis of complex 3 is similar to that of complex 1: compound 3c (0.45 g, 0.732 mmol) was used instead of compound 1c. 0.266 g of solid was obtained with a yield of 41%. MS (m / z): 888.33 (M+1)

[0075] Example 3: Synthesis of Complex 4

[0076] Synthesis of compound 4a:

[0077]

[0078] The synthesis of compound 4a was similar to that of compound 1a: 3,5-dimethylaniline (2.05 g, 16.96 mmol) was used instead of aminobenzene. 1.903 g of solid was obtained with a yield of 71%. MS (m / z): 317.45 (M+1)

[0079] Synthesis of compound 4b:

[0080]

[0081] The synthesis of compound 4b was similar to that of compound 1b: compound 4a (2.00 g, 6.32 mmol) was used instead of compound 1a. 1.939 g of solid was obtained with a yield of 74%. MS (m / z): 415.25 (M+1)

[0082] Synthesis of compound 4c:

[0083]

[0084] The synthesis of compound 4c was similar to that of compound 1c: compound 4b (1.00 g, 2.41 mmol) was used instead of compound 1b. 0.513 g of solid was obtained with a yield of 38%. MS (m / z): 559.86 (M+1)

[0085] Synthesis of complex 4:

[0086]

[0087] The synthesis of complex 4 is similar to that of complex 1: Compound 4c (0.20 g, 0.358 mmol) was used instead of compound 1c. 0.110 g of solid was obtained with a yield of 37%. MS (m / z): 832.77 (M+1)

[0088] Example 4: Synthesis of Complex 57

[0089] Synthesis of compound 57a:

[0090]

[0091] Under nitrogen, palladium acetate (0.056 g, 0.25 mmol) and 2,2′-bis(diphenylphosphine)-1,1′-binaphthyl (0.164 g, 0.25 mmol) were dissolved in 30 mL of toluene. Then 2-chloro-3-iodopyridine (2.00 g, 8.35 mmol), aminobenzene (1.94 g, 20.88 mmol) and cesium carbonate (13.61 g, 41.76 mmol) were added to the suspension and refluxed at 120°C for 12 h. After the reaction was completed, it was cooled to room temperature, filtered through diatomaceous earth, and the filtrate was extracted with water. The organic phase was dried with anhydrous sodium sulfate and adsorbed on silica gel, purified by column chromatography (pure dichloromethane), and finally slurried with methanol and the solvent was removed in vacuo. 1.215 g of white solid was obtained. The yield was 56%. MS (m / z): 262.33 (M+1)

[0092] Synthesis of compound 57b:

[0093]

[0094] The synthesis of compound 57b was similar to compound 1b: compound 57a (2.00 g, 7.65 mmol) was used instead of compound 1a. 1.953 g of solid was obtained with a yield of 71%. MS (m / z): 360.13 (M+1)

[0095] Synthesis of compound 57c:

[0096]

[0097] The synthesis of compound 57c was similar to compound 1c: compound 57b (1.00 g, 2.78 mmol) was used instead of compound 1b. 0.614 g of solid was obtained with a yield of 44%. MS (m / z): 504.74 (M+1)

[0098] Synthesis of complex 57:

[0099]

[0100] The synthesis of complex 57 was similar to that of complex 1: compound 57c (0.45 g, 0.893 mmol) was used instead of compound 1c. 0.281 g of solid was obtained with a yield of 45%. MS (m / z): 777.65 (M+1)

[0101] Example 5: Synthesis of Complex 59

[0102] Synthesis of compound 59a:

[0103]

[0104] The synthesis of compound 59a was similar to that of compound 57a: 4-tert-butylaniline (3.12 g, 20.88 mmol) was used instead of aminobenzene. 2.215 g of solid was obtained with a yield of 71%. MS (m / z): 374.54 (M+1)

[0105] Synthesis of compound 59b:

[0106]

[0107] The synthesis of compound 59b was similar to compound 1b: compound 59a (2.00 g, 5.35 mmol) was used instead of compound 1a. 1.664 g of solid was obtained with a yield of 66%. MS (m / z): 472.35 (M+1)

[0108] Synthesis of compound 59c:

[0109]

[0110] The synthesis of compound 59c was similar to that of compound 1c: compound 59b (1.00 g, 2.41 mmol) was used instead of compound 1b. 0.513 g of solid was obtained with a yield of 39%. MS (m / z): 616.96 (M+1)

[0111] Synthesis of complex 59:

[0112]

[0113] The synthesis of complex 59 was similar to that of complex 1: compound 59c (0.45 g, 0.731 mmol) was used instead of compound 1c. 0.241 g of solid was obtained with a yield of 41%. MS (m / z): 889.87 (M+1)

[0114] Example 6: Synthesis of Complex 60

[0115] Synthesis of compound 60a:

[0116]

[0117] The synthesis of compound 60a was similar to compound 57a: 3,5-dimethylaniline (2.53 g, 20.88 mmol) was used instead of aminobenzene. 1.464 g of solid was obtained with a yield of 55%. MS (m / z): 318.44 (M+1)

[0118] Synthesis of compound 60b:

[0119]

[0120] The synthesis of compound 60b was similar to compound 1b: compound 60a (2.00 g, 6.30 mmol) was used instead of compound 1a. 2.017 g of solid was obtained with a yield of 77%. MS (m / z): 416.24 (M+1)

[0121] Synthesis of compound 60c:

[0122]

[0123] The synthesis of compound 60c was similar to that of compound 1c: compound 60b (1.00 g, 2.41 mmol) was used instead of compound 1b. 0.513 g of solid was obtained with a yield of 38%. MS (m / z): 560.85 (M+1)

[0124] Synthesis of complex 60:

[0125]

[0126] The synthesis of complex 60 was similar to that of complex 1: compound 60c (0.45 g, 0.804 mmol) was used instead of compound 1c. 0.312 g of solid was obtained with a yield of 47%. MS (m / z): 833.76 (M+1)

[0127] Example 7: Synthesis of Complex 113

[0128] Synthesis of compound 113a:

[0129]

[0130] Mix 2,3-dichloropyrazine (6.00 g, 40.28 mmol) and aminobenzene (8.25 g, 88.61 mmol) and react at 160°C for 3 h. After the reaction is completed, cool to room temperature, dissolve with appropriate amounts of 25% sodium hydroxide aqueous solution and dichloromethane, take the organic phase and adsorb it on silica gel, and purify it by column chromatography (dichloromethane: petroleum ether = 1:9) to obtain 6.610 g of solid. Yield 63%. MS (m / z): 263.32 (M+1)

[0131] Synthesis of compound 113b:

[0132]

[0133] The synthesis of compound 113b was similar to compound 1b: compound 113a (2.00 g, 7.62 mmol) was used instead of compound 1a. 2.228 g of solid was obtained with a yield of 81%. MS (m / z): 361.12 (M+1)

[0134] Synthesis of compound 113c:

[0135]

[0136] The synthesis of compound 113c was similar to that of compound 1c: compound 113b (1.00 g, 2.78 mmol) was used instead of compound 1b. 0.714 g of solid was obtained with a yield of 51%. MS (m / z): 505.73 (M+1)

[0137] Synthesis of complex 113:

[0138]

[0139] The synthesis of complex 113 was similar to that of complex 1: compound 113c (0.45 g, 0.892 mmol) was used instead of compound 1c. 0.291 g of solid was obtained with a yield of 46%. MS (m / z): 778.64 (M+1)

[0140] Example 8: Synthesis of Complex 115

[0141] Synthesis of compound 115a:

[0142]

[0143] The synthesis of compound 115a was similar to that of compound 113a: 4-tert-butylaniline (13.22 g, 88.61 mmol) was used instead of aminobenzene. 6.948 g of solid was obtained with a yield of 46%. MS (m / z): 375.53 (M+1)

[0144] Synthesis of compound 115b:

[0145]

[0146] The synthesis of compound 115b was similar to compound 1b: compound 115a (2.00 g, 5.34 mmol) was used instead of compound 1a. 1.664 g of solid was obtained with a yield of 66%. MS (m / z): 473.34 (M+1)

[0147] Synthesis of compound 115c:

[0148]

[0149] The synthesis of compound 115c was similar to compound 1c: compound 115b (1.00 g, 2.12 mmol) was used instead of compound 1b. 0.613 g of solid was obtained with a yield of 47%. MS (m / z): 617.94 (M+1)

[0150] Synthesis of complex 115:

[0151]

[0152] The synthesis of complex 115 was similar to that of complex 1: compound 59c (0.45 g, 0.731 mmol) was used instead of compound 1c. 0.206 g of solid was obtained with a yield of 35%. MS (m / z): 890.86 (M+1)

[0153] Example 9: Synthesis of Complex 116

[0154] Synthesis of compound 116a:

[0155]

[0156] The synthesis of compound 116a was similar to that of compound 113a: 3,5-dimethylaniline (10.74 g, 88.61 mmol) was used instead of aminobenzene. 6.501 g of solid was obtained with a yield of 51%. MS (m / z): 319.42 (M+1)

[0157] Synthesis of compound 116b:

[0158]

[0159] The synthesis of compound 116b was similar to compound 1b: compound 116a (2.00 g, 6.28 mmol) was used instead of compound 1a. 2.170 g of solid was obtained with a yield of 83%. MS (m / z): 417.23 (M+1)

[0160] Synthesis of compound 116c:

[0161]

[0162] The synthesis of compound 116c was similar to that of compound 1c: compound 116b (1.00 g, 2.40 mmol) was used instead of compound 1b. 0.627 g of solid was obtained with a yield of 46%. MS (m / z): 561.84 (M+1)

[0163] Synthesis of complex 116:

[0164]

[0165] The synthesis of complex 116 was similar to that of complex 1: compound 116c (0.40 g, 0.712 mmol) was used instead of compound 1c. 0.249 g of solid was obtained with a yield of 42%. MS (m / z): 834.75 (M+1)

[0166] Example 10: Synthesis of Complex 169

[0167] Synthesis of compound 169c:

[0168]

[0169] Compound 1b (0.50 g, 1.40 mmol), palladium chloride (0.396 g, 2.23 mmol), sodium tert-butoxide (0.268 g, 2.79 mmol) were added to 10 mL THF under nitrogen and refluxed at 80 ° C for 12 h. After the reaction was completed, the solid was slurried with n-hexane and the solvent was removed in vacuo. 0.391 g of solid was obtained with a yield of 68%. MS (m / z): 413.21 (M+1)

[0170] Synthesis of compound 169:

[0171]

[0172] The synthesis of complex 169 was similar to that of complex 1: compound 169c (0.450 g, 1.09 mmol) was used instead of compound 1c. 0.489 g of solid was obtained with a yield of 72%. MS (m / z): 686.12 (M+1)

[0173] Example 11: Synthesis of Complex 181

[0174] Synthesis of compound 181c:

[0175]

[0176] Compound 1b (0.50 g, 1.40 mmol) and silver oxide (0.196 g, 0.846 mmol) were added to 10 mL DCM under nitrogen and reacted at room temperature for 12 h. After the reaction, the solid was slurried with n-hexane and the solvent was removed in vacuo. 0.281 g of solid was obtained with a yield of 40%. MS (m / z): 370.33 (M+1)

[0177] Synthesis of compound 181:

[0178]

[0179] The synthesis of complex 181 was similar to that of complex 1: compound 181c (0.450 g, 1.22 mmol) was used instead of compound 1c. 0.446 g of solid was obtained with a yield of 60%. MS (m / z): 687.57 (M+1)

[0180] Example 12: Synthesis of Complex 193

[0181] Synthesis of compound 193c:

[0182]

[0183] The synthesis of complex 193c was similar to that of compound 169c: compound 193c (0.276 g, 2.79 mmol) was used instead of compound 169c. 0.421 g of solid was obtained with a yield of 82%. MS (m / z): 370.33 (M+1)

[0184] Synthesis of compound 193:

[0185]

[0186] The synthesis of complex 193 was similar to that of complex 1: compound 193c (0.450 g, 1.22 mmol) was used instead of compound 1c. 0.401 g of solid was obtained with a yield of 56%. MS (m / z): 643.25 (M+1)

[0187] Those skilled in the art should be aware that the above preparation methods are only several illustrative examples, and those skilled in the art can obtain other compound structures of the present invention by improving them.

[0188] Examples 13-24 and Comparative Example 1:

[0189] A mixed film of gold complexes (1, 3, 4, 57, 59, 60, 113, 115, 116, 169, 181, 193) doped in an organic donor TAPC was prepared by a solution spin coating method, and the weight ratio of the two was: complex acceptor / TAPC = 20% / 80%; a solid film of an organic acceptor TRZ (structure see the figure below) doped in an organic donor TAPC was prepared by a solution spin coating method, and the weight ratio of the two was: complex acceptor / organic donor = 20% / 80%.

[0190] The photophysical properties of the above films are listed in Table 1.

[0191]

[0192] Table 1

[0193]

[0194]

[0195] The complex acceptor material and the organic donor material doped emit strong light, and compared with the donor or acceptor, there is a significant red shift (attached Figure 1-3 Some representative emission spectra are listed), indicating that the two form an exciplex. The exciplex formed by the organic donor and the complex acceptor material in the present invention is significantly higher than the mixture film of the organic donor TAPC and the organic acceptor (TRZ), and the excited state lifetime is shorter, which confirms the feasibility of using the gold complex acceptor to construct a high-performance exciplex luminescent material.

[0196] Embodiment 25:

[0197] The donor and acceptor material mixture of the present invention is used to construct an exciplex luminescent material to prepare an organic light-emitting diode. The device structure is shown in the attached Figure 4 .

[0198] First, the transparent conductive ITO glass substrate 10 (with the anode 20 thereon) is washed with a detergent solution and deionized water, ethanol, acetone, and deionized water in sequence, and then treated with oxygen plasma for 30 seconds.

[0199] Then, a 40 nm thick PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate)) was spin-coated on the ITO as the hole injection layer 30 . PEDOT:PSS is a mixture.

[0200] Then, a 30 nm thick light emitting layer 40 is spin-coated on the hole injection layer. The light emitting layer is composed of a mixed doping of gold complex 1 (20%) and TAPC (80%).

[0201] Then, TmPyPB was evaporated to a thickness of 40 nm on the light-emitting layer as the electron transport layer 50 .

[0202] Finally, 1 nm LiF was evaporated as the electron injection layer 60 and 100 nm Al was evaporated as the device cathode 70 .

[0203] Example 26: Using complex 3 instead of complex 1, an organic light emitting diode was prepared using the method described in Example 25.

[0204] Example 27: Using complex 4 instead of complex 1, an organic light emitting diode was prepared using the method described in Example 25.

[0205] Example 28: Using complex 57 instead of complex 1, an organic light emitting diode was prepared using the method described in Example 25.

[0206] Example 29: Complex 59 was used to replace complex 1, and an organic light emitting diode was prepared using the method described in Example 25.

[0207] Example 30: Complex 60 was used to replace complex 1, and an organic light emitting diode was prepared using the method described in Example 25.

[0208] Example 31: Complex 113 was used to replace complex 1, and an organic light-emitting diode was prepared using the method described in Example 25.

[0209] Example 32: Complex 115 was used to replace complex 1, and an organic light-emitting diode was prepared using the method described in Example 25.

[0210] Example 33: Using complex 116 instead of complex 1, an organic light-emitting diode was prepared using the method described in Example 25.

[0211] Example 34: Using complex 169 instead of complex 1, an organic light-emitting diode was prepared using the method described in Example 25.

[0212] Example 35: Using complex 181 instead of complex 1, an organic light emitting diode was prepared using the method described in Example 25.

[0213] Example 36: Using complex 193 instead of complex 1, an organic light emitting diode was prepared using the method described in Example 25.

[0214] Comparative Example 2:

[0215] An organic light emitting diode was prepared by the method described in Example 25 using TRZ instead of complex 1.

[0216] The device performance of the organic electroluminescent devices in Examples 25-36 and Comparative Example 2 at a current density of 10 mA / cm2 is listed in Table 2:

[0217] Table 2

[0218]

[0219] It can be seen from the data in Table 2 that under the same conditions, the metal complex acceptor material of the present invention is used in combination with an organic donor in an organic light-emitting diode, which has a lower driving voltage and a higher luminous efficiency. In addition, the device life of the organic light-emitting diode based on the complex of the present invention is significantly better than that of the exciplex luminescent material in the comparative example, and has a good application prospect.

[0220] The above-mentioned various embodiments are only used as some representative examples and are not used to limit the scope of the present invention. Without departing from the spirit of the present invention, the various materials and structures in the present invention can be replaced by other materials and structures. It should be understood that those skilled in the art can make many modifications and changes based on the thinking of the present invention without creative work. Therefore, the technical solutions that can be obtained by technical personnel through analysis, reasoning or partial research on the basis of the prior art should all be within the scope of protection limited by the claims.

Claims

1. The metal complex receptor material is a compound having the structure of formula (I): in: R 1 To R 6 are substituents, each independently selected from the group consisting of deuterium, halogen, aldehyde, cyano, substituted or unsubstituted alkylsulfonyl having 1 to 6 carbon atoms, substituted or unsubstituted arylsulfonyl having 6 to 30 carbon atoms, substituted or unsubstituted alkyl having 1 to 6 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted alkoxy having 1 to 20 carbon atoms, substituted or unsubstituted aryl having 6 to 30 carbon atoms, substituted or unsubstituted heteroaryl having 3 to 30 carbon atoms, or any two adjacent substituents connected or fused to form a ring; The heteroatom in the heteroaryl group is N, S or O, and the substitution is substitution by D, F, or C1-C4 alkyl; M is selected from: gold, silver, palladium or copper; X1 and X2 are each independently C or N; a1 to a4 are integers of 0-5, and when a1 is 2 or greater, two R 1 The groups are the same or different from each other. When a2 is 2 or greater, the two R 2 The groups are the same or different from each other. When a3 is 2 or greater, the two R 3 The groups are the same or different from each other. When a4 is 2 or greater, the two R 4 The groups are the same or different from each other; a5 and a6 are integers of 0-4, and when a5 is 2 or greater, the two R 5 The groups are the same or different from each other. When a6 is 2 or greater, the two R 6 The groups are the same or different from each other; When a1 to a6 are zero, R 1 To R 6 The substituent is not present.

2. The metal complex acceptor material according to claim 1, wherein R 1 To R 6 Each is independently selected from the group consisting of deuterium, a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 20 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, and a substituted or unsubstituted heteroaryl group having 3 to 30 carbon atoms.

3. The metal complex acceptor material according to claim 1, wherein: R 1 To R 2 Each is independently selected from hydrogen, deuterium, a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 20 carbon atoms, and a3 to a6 are zero.

4. The metal complex acceptor material according to claim 1, wherein: X1 and X2 are both N.

5. The metal complex acceptor material according to any one of claims 1 to 4, wherein: M stands for gold.

6. The metal complex receptor material according to claim 1, having one of the following structures:

7. An exciplex luminescent material, comprising 5% to 95% by mass of a metal complex acceptor material according to any one of claims 1 to 6 and 95% to 5% by mass of an organic donor material, wherein the organic donor material molecule has one of the following structures:

8. The exciplex luminescent material according to claim 7, which is composed of 5%-20% of metal complex acceptor material and 95%-80% of organic donor material molecules in a mass ratio.

9. Use of the exciplex luminescent material according to claim 7 or 8 in an organic optoelectronic device, wherein the organic optoelectronic device is an organic light emitting diode, an organic thin film transistor, an organic photovoltaic device, a light emitting electrochemical cell and a chemical sensor.

10. An organic light emitting diode, comprising a cathode, an anode and an organic layer, wherein the organic layer is one or more of a hole injection layer, a hole transport layer, a light emitting layer, a hole blocking layer, an electron injection layer and an electron transport layer, and at least one of the hole injection layer, the hole transport layer, the hole blocking layer, the electron injection layer, the light emitting layer and the electron transport layer contains the exciplex light emitting material according to claim 7 or 8.

Citation Information

Patent Citations

  • N-heterocyclic carbene palladium complex crystal and synthetic method thereof and application of n-heterocyclic carbene palladium complex crystal in preparation of alpha,beta-unsaturated ketone compounds

    CN110452270A

  • Metal complex and organic electroluminescent device

    CN115490710A

  • Metal complex and organic electroluminescent device

    CN115700250A

  • Organic electroluminescent materials and devices

    US20240188319A1